Design Participativo para cultura patrimonial: contribuições metodológicas no bairro do Desterro - Centro histórico - São Luís-MA - PINHEIRO, Nathalia Rodrigues (2021)
This research aims to promote and enhance the Cultural Heritage of the Historical Center of São Luís / MA through techniques of Participatory Design. The data set collection contemplate the historic neighborhood of Desterro and its residents knowledge, the methods and techniques of social dialogue were inspired by the considerations of Manzini (2017) and Halse (2013), and took place in the community house from the neighborhood of Desterro, a Casa do Bairro. The playfulness promoted during the meetings brought together the creation of a cartographic representation of the experiences, translated into a board game, which was the result of a collaborative construction and was called “Um olhar para o Desterro”. The final product of this research, the board, became an instrument for recording local culture and an edifying tool in education, aiming the heritage valuing for people of all ages. As a general synthesis of this work and experiences achieved, it was presented a proposal for a methodological approach for future research in the heritage environment.